Determination of αs from hadronic event shapes in e+e− annihilation at 192 ⩽s⩽ 208 GeV - Dova, María Teresa (2002)
Results are presented from a study of the structure of high energy hadronic events recorded by the L3 detector at √s 192 GeV. The distributions of several event shape variables are compared to resummed O(α2 s ) QCD calculations. We determine the strong coupling constant at three average centre-of-mass energies: 194.4, 200.2 and 206.2 GeV. These measurements, combined with previous L3 measurements at lower energies, demonstrate the running of αs as expected in QCD and yield αs(mZ) = 0.1227 ± 0.0012 ± 0.0058, where the first uncertainty is experimental and the second is theoretical.